Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Sistem Administrasi Menunggal Satu Atap Kabupaten Sidenreng Rappang - Aziz, Acep Purnama Abdul; H, Haeril; Nurwafiyyah, Auliyah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to find out whether there is an influence between work discipline and employee performance at the One-Stop Manunggal Administration System Office of Sidenreng Rappang Regency. The population in this study is all employees at the One-Stop Manunggal Administration System Office of Sidenreng Rappang Regency which totals 45 employees, and the sample drawing technique used is saturated sampling. Data were obtained from primary data and secondary data. The data collection techniques used are observation, interviews, questionnaires and documentation. The method used in this study is an associative quantitative research method. Based on the results of the analysis that has been carried out, it is shown that the work discipline variable has a positive effect on employee performance at the Sidenreng Rappang Regency One-Stop Administrative System Office because the significant value of the t-test (0.002) is smaller than 0.5. The contribution of work discipline to employee performance can be said to be significant from the analysis that has been carried out at the One-Stop Manunggal Administration System Office of Sidenreng Rappang Regency. And it is suggested to the next researcher that it is hoped that this research can be developed again by adding other variables or indicators that can affect employee performance.